2015
DOI: 10.1111/jace.13411
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Pyrochlore Bismuth Zinc Niobate Thin Films for High‐Temperature Dielectric Energy Storage

Abstract: Thin films of cubic pyrochlore bismuth zinc niobate, a lead-free dielectric, were fabricated using a solution chemistry based upon the Pechini method. Scanning electron microscopy confirmed that the films are smooth and mostly dense. The films exhibit a dielectric constant of 145 AE 5, a low dielectric loss of 0.00065 AE 0.0001, and a room temperature, 1 kHz maximum field of approximately 4.7 MV/cm. At frequencies of 100 Hz and 10 kHz, the maximum field sustained by the material increased to 5.0 MV/cm and 5.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…As reported, not only dielectric breakdown but also dielectric polarization is dominant to energy storage performances in dielectrics . Until now, some Bi‐based materials suitable for energy storage were reported by researchers, such as sodium bismuth titanate, bismuth zinc niobate (cubic pyrochlore structure) and BiFeO 3 . Li et al reported recoverable energy storage density of 13.02 ± 0.39 J/cm 3 in 0.9 (Bi 0.5 Na 0.5 )TiO 3 ‐0.1 PbTiO 3 thin film.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As reported, not only dielectric breakdown but also dielectric polarization is dominant to energy storage performances in dielectrics . Until now, some Bi‐based materials suitable for energy storage were reported by researchers, such as sodium bismuth titanate, bismuth zinc niobate (cubic pyrochlore structure) and BiFeO 3 . Li et al reported recoverable energy storage density of 13.02 ± 0.39 J/cm 3 in 0.9 (Bi 0.5 Na 0.5 )TiO 3 ‐0.1 PbTiO 3 thin film.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al reported recoverable energy storage density of 13.02 ± 0.39 J/cm 3 in 0.9 (Bi 0.5 Na 0.5 )TiO 3 ‐0.1 PbTiO 3 thin film. Michael et al achieved large energy storage performances with a maximum energy storage of ~46.7 ± 1.7 J/cm 3 at 100 Hz in Bi 1.5 Zn 0.9 Nb 1.5 O 6.9 thin film and 66.9 ± 2.4 J/cm 3 in Bi 1.5 Zn 0.9 Nb 1.4 Ta 0.1 O 6.9 thin film, respectively. Although the energy storage performance of this system is comparable to that of lead‐containing materials, the cost of the expensive raw materials niobium ethoxide will limit its mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric capacitors with the physical nature of ultrafast charge/discharge kinetics are promising candidates for energy storage devices . Moreover, due to the capability of delivering charges in an extremely short time, they are also widely used in today's advanced high‐power electric and electronic systems, from smart grids and switch power in consumer use to electric guns and direct energy weapons in military service, from oil drilling devices and spacecraft in harsh environment to magnetic resonance imaging and implantable defibrillators in medical system . In recent years, toward the demand of miniaturization, lightweight, and integration of electric and electronic devices, high‐energy density dielectric capacitors of reduced size are thus strongly desirable …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Moreover, due to the capability of delivering charges in an extremely short time, they are also widely used in today's advanced high-power electric and electronic systems, from smart grids and switch power in consumer use to electric guns and direct energy weapons in military service, from oil drilling devices and spacecraft in harsh environment to magnetic resonance imaging and implantable defibrillators in medical system. [11][12][13][14][15] In recent years, toward the demand of miniaturization, lightweight, and integration of electric and electronic devices, high-energy density dielectric capacitors of reduced size are thus strongly desirable. 13,16 In principle, the energy storage density (W) of dielectrics is determined by the integral of the applied electric field (E) with respect to the electric displacement (D) as W ¼ R EdD.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical energy storage capacitors for pulsed power applications need to accumulate a large amount of energy with fast discharge capability and high frequencies on the order of several kilohertz. 17 Low high-electric field loss pulsed power capacitors find uses in a wide variety of applications from industrial lasers used for cutting and welding, to critical biomedical devices, such as heart defibrillators and X-ray equipment. 18,19 Pocket sized pulsed power capacitors are utilized in the development of implantable defibrillators.…”
Section: Introductionmentioning
confidence: 99%